Safety, efficacy, actions, and patient acceptability of drospirenone/ethinyl estradiol contraceptive pills in the treatment of premenstrual dysphoric disorder - Lesley L Breech; Paula K Braverman (Dove Medical Press, 2009)
Lesley L Breech, Paula K BravermanDivision of Adolescent Medicine, Department of Pediatrics, Cincinnati Children’s Hospital Medical Center, University of Cincinnati College of Medicine, Cincinnati, OH, USAAbstract: Premenstrual dysphoric disorder (PMDD) is estimated to affect 3%–8% of reproductive age women. Multiple therapeutic modalities have been evaluated with varying efficacy for the associated somatic and mood symptoms. The majority of older studies had shown that oral contraceptive pills (OCs) were most effective for the physical symptoms. However, newer OCs containing a novel progestin, drospirenone, have shown promise in alleviating both the somatic and affective/behavioral symptoms. This progestin, which is a derivative of spironolactone, has both antimineralocorticoid and antiandrogenic activity. A 24/4 formulation containing 20 µg of ethinyl estradiol has been found effective in randomized double-blind placebo-controlled trials utilizing established scales documenting symptoms associated with PMDD. Multiple studies have shown that drospirenone-containing OCs are safe without evidence of clinically adverse effects on carbohydrate metabolism, lipids, blood pressure, weight, serum potassium or increased thrombotic events compared to other low dose OCs. In addition, significant improvements have been demonstrated in acne, hirsutism, and fluid retention symptoms. Several open label studies demonstrated good patient compliance and reported satisfaction with the method. Because of the significant placebo effect demonstrated in the blinded placebo-controlled trials, additional large randomized placebo-controlled trials are needed to confirm the efficacy of the drospirenone OCs in the treatment of PMDD. However, this OC formulation appears to be a promising therapeutic modality.Keywords: drospirenone, premenstrual dysphoric disorder, premenstrual syndrome, oral contraceptive pill